Impact of pillar configuration on the amphiphobicity of micro-patterned polymer surface. (October 2018) - Yao, Wenhui; Li, Oi Lun; Kang, Young-Joon; Jeong, Myung-Yung; Cho, Young-Rae
Abstract: Hydrophobic surfaces are easily contaminated by oil owing to its lower surface tension, which significantly limits their potential applications. In this study, micro-patterned surfaces with cylindrical or square pillar arrays were fabricated on a polycarbonate substrate by the thermal imprinting process. The geometry and size of the pillars were varied to obtain different samples, whereas the height of the pillars was kept constant. The surface of each micro-patterned sample was fluorinated with perfluorooctanoic acid. With the aim of characterizing the wetting behavior of the samples, droplets of water and oily liquids with different surface tensions were employed to measure the contact angles. In addition, the applicability of the Wenzel and Cassie equations for explaining the wetting mechanisms of droplets on the surfaces of the micro-patterned samples was systematically investigated. The prediction obtained using the Wenzel equation was found to differ considerably from the experimental results, whereas the Cassie equation was found to be acceptable for satisfactorily explaining the wetting behaviors of liquids on the micro-patterned samples. The main factor influencing the surface wettability of the micro-patterned sample was not the pillar geometry, but rather the pillar configuration, e.g., the solid area fraction, groove fraction, and spacing between pillars. Highlights: Micro-patterned surface with pillar array is formed by a thermal imprinting method. The micro-patterned surface is repellent to both water and oily liquids. Effect of pillar configuration on the amphiphobicity is studied. Wetting mechanism of liquid droplet on the micro-patterned surface is proposed.